Novel and unexpected role for the tumor suppressor ARF in viral infection surveillance. (November 2007) - Garcia, Maria Angel; Muññoz-Fontela, Cesar; Collado, Manuel; Marcos-Villar, Laura; Esteban, Mariano; Rivas, Carmen
Virus infection induces the synthesis of interferons which, in turn, stimulate the expression of hundreds of cellular genes, any of those denominated viral-stress-inducible genes. Among interferon-upregulated genes, also triggered by oncogenic viruses, several tumor-suppressor genes can also be listed. A correlation between the tumor suppressor alternative reading frame (ARF) and virus replication was noted some time ago. Yang and colleagues in 2001 demonstrated that p14ARF modulated the cytolytic effect of the E1B-deleted adenovirus ONYX-015 in mesothelioma cells with wild-type p53, and expression of p14ARF attenuated the cytolytic effect of the virus. Later, in 2006, Garcia and colleagues identified ARF as a gene product with a role in reducing the sensitivity of cells to infection by several viruses, showing an inverse relationship between doses of ARF and levels of virus replication. Additionally, the same authors presented a number of experiments designed to illustrate the molecular mechanisms underlying the decrease of virus replication upon ARF overexpression, demonstrating a p53-independent ARF function. ARF is the latest tumor suppressor added to the list of the cellular genes upregulated by type I interferon that possesses antiviral activity. The antiviral role of other tumor suppressor pathways targeted by both interferons and oncogenic viruses requires further investigation.